(untitled) (Филологические заметки, 2019)
I have chosen to illustrate the application of Fabb and Halle’s theory of meter in poetry with expressions about ravens that are formulas from three different oral poetic traditions. They represent the epics from the Balkans, English ballads and Latvian narrative and lyric dainas. Let it be the beginning for the exploration of commons aspects of formulae that go well beyond metrics.